Fully Balanced Fluids do not Improve Microvascular Oxygenation, Acidosis and Renal Function in a Rat Model of Endotoxemia. Issue 1 (July 2016) - Ergin, Bulent; Zafrani, Lara; Kandil, Asli; Baasner, Silke; Lupp, Corinna; Demirci, Cihan; Westphal, Martin; Ince, Can
Abstract : ABSTRACT: The expectation of fluid therapy in patients with septic shock is that it corrects hypovolemia, with the aim of restoring tissue perfusion and oxygenation and organ function. This study investigated whether different types of resuscitation fluids were effective in improving renal microcirculatory oxygenation, acidosis, oxidative stress, and renal function in a rat model of endotoxemic shock. Five groups of rats were used: a sham group, a lipopolysaccharide (LPS) group, and three LPS groups that received 30 mL/kg/h of 0.9% sodium chloride (0.9% NaCl), a new bicarbonate buffered crystalloid solution closely resembling the composition of plasma (FB-Cxt) or a hydroxyethyl starch-ringer acetate solution. Systemic hemodynamic variables, renal blood flow, microvascular oxygenation, oxidative/nitrosative stress, and renal function were measured. LPS-induced shock was only partially resolved by fluid administration. Animals became arterially hypotensive despite adequate central venous pressure. Hydroxyethyl starch-ringer acetate was more effective at improving arterial pressures and renal blood flow than 0.9% NaCl or FB-Cxt. Fluids had marginal effects on pH and HCO3 − levels irrespective of the buffer, or on renal μPO2 and dysfunction. Colloids increased the markers of renal oxidative stress ( P < 0.001), whereas unbalanced crystalloids increased the markers of nitrosative stress during sepsis ( P < 0.01). Endotoxemia-induced acidosis and decreases in renal μPO2 or renal injury were not corrected solely by fluid resuscitation, irrespective of the buffer of the fluid. Our study supported the idea that fluids must be supplemented by other compounds that specifically correct renal inflammation and oxygenation to be effective in resolving septic shock-induced renal failure. Abstract : Supplemental Digital Content is available in the text